Developing an AI-Powered Algorithm for Automated Detection and Classification of Dental Caries from Intraoral Radiographs: A Machine Learning Approach - Mohammad Haider (Journal of Pharmacy and Bioallied Sciences)
This systematic review aims to assess the diagnostic accuracy of artificial intelligence (AI) models specifically developed for detecting and classifying dental caries. A comprehensive electronic literature search was performed on the PubMed, Web of Science, SCOPUS, and Embase databases. The search yielded a total of 397 results. We examined 10 articles that satisfied the selection criteria. In summary, AI-based models show high diagnostic accuracy in recognizing dental caries by analyzing dental radiography pictures.